Relocation in labour-intensive sectors from Southern Europe: a threat or a forward looking strategy? - Cesário, M. (2012)
Notwithstanding the present context of economic globalisation, we admit the role of territorial agglomerations for the competitiveness of regions and firms and we ask about the impact of firms’ technological adjustment strategies to the territories themselves, namely in terms of regional employment and income perspectives? In order to empirically test if technical changes are associated with the variation of employment levels and skills, a survey application to a sample of 167 SMEs from textile, clothes and leather (TCL) sectors located in Southern Europe is used. Using statistical procedures, the importance of several predictor variables to the variation of firms’ employment was evaluated. The results confirm that technical change is both skill-biased as well as positively associated with employment growth. Firms investing in new plant and equipment and firms investing in the development of new products are more likely to increase employment than the others. Also, firms hiring in these sectors, look for adequate qualifications, in particular regarding the ability to work with internet tools. We argue that delocalisation can be transformed in a positive strategic reality if TCL firms are able to lower production costs and logistics in order to make the necessary technological investments.